CoNi-based metal–organic framework nanoarrays supported on carbon cloth as bifunctional electrocatalysts for efficient water-splitting. (20th January 2020) - Bai, Xiao-Jue; Chen, Huan; Li, Yu-Nong; Shao, Lei; Ma, Jun-Chao; Li, Lin-Lin; Chen, Jun-Yi; Wang, Tie-Qiang; Zhang, Xue-Min; Zhang, Li-Ying; Fu, Yu; Qi, Wei
Abstract : CoNi-based metal–organic framework (MOF) nanoarrays supported on carbon cloth can be used as an efficient bifunctional electrocatalyst for overall water splitting. Abstract : Herein, CoNi-based metal–organic framework nanoarrays were prepared on carbon cloth using a spray synthetic strategy at room temperature. The nanoarrays with a large external surface area show a low overpotential of 251 mV at 10 mA cm −2 for the OER, 135 mV at −10 mA cm −2 for the HER, and 395 mV at 10 mA cm −2 for overall water splitting, as well as high durability under alkaline conditions.